Persepsi Mengenai Implementasi Konsep Negara Hukum Dan Demokrasi(Studi Kasus pada Anggota Badan Permusyawaratan Desa (BPD) Desa Kingkang Kecamatan Wonosari Kabupaten Klaten Tahun 2015) - Irawati, Jatik, Drs. Achmad Muthali'in, M.Si (2015)
Indonesian state implement the concept of a state of law and democracy in the administration of government. But not all citizens understand the meaning of a state of law and democracy. For this research focuses on understanding and perceptions regarding the implementation of the concept of rule of law and democracy at the BPD. Election of members of BPD as a research subject can not be separated from BPD institutions as one of the elements of village administration. The purpose of this study was to describe the understanding and perceptions regarding the implementation of the concept of rule of law and democracy in BPD members Kingkang Village, Wonosari Subdistrict of Klaten. This study is a qualitative research, with data collection techniques through observation, interviews, and documentation. Validity of data with triangulation data sources and data collection. Data analysis was performed with an interactive model of data collection, data reduction, data presentation, and conclusion. Research subject BPD members Kingkang Village, Wonosari subdistrict of Klaten. Results of this study illustrate that the understanding and perception of the implementation of the concept of rule of law and democracy at the BPD members Kingkang Village Wonosari Subdistrict of Klaten as a whole has been good. This is proven by the relevance of the results of observation, interviews, and review documentation. In conclusion perception pulled-nai implementation of the concept of a state of law and democracy are determined by each indicator in BPD members are good and in accordance with the literature study.